Caracterização dos acoplamentos fase-amplitude na região CA1 do hopocampo - Teixeira, Robson Scheffer (2011)
Brain oscillation are not completely independent, but able to interact with each other through cross-frequency coupling (CFC) in at least four different ways: power-to-power, phase-to-phase, phase-to-frequency and phase-to-power. Recent evidence suggests that not only the rhythms per se, but also their interactions are involved in the execution of cognitive tasks, mainly those requiring selective attention, information flow and memory consolidation. It was recently proposed that fast gamma oscillations (60 150 Hz) convey spatial information from the medial entorhinal cortex to the CA1 region of the hippocampus by means of theta (4-12 Hz) phase coupling. Despite these findings, however, little is known about general characteristics of CFCs in several brain regions. In this work we recorded local field potentials using multielectrode arrays aimed at the CA1 region of the dorsal hippocampus for chronic recording. Cross-frequency coupling was evaluated by using comodulogram analysis, a CFC tool recently developted (Tort et al. 2008, Tort et al. 2010). All data analyses were performed using MATLAB (MathWorks Inc). Here we describe two functionally distinct oscillations within the fast gamma frequency range, both coupled to the theta rhythm during active exploration and REM sleep: an oscillation with peak activity at ~80 Hz, and a faster oscillation centered at ~140 Hz. The two oscillations are differentially modulated by the phase of theta depending on the CA1 layer; theta-80 Hz coupling is strongest at stratum lacunosum-moleculare, while theta-140 Hz coupling is strongest at stratum oriens-alveus. This laminar profile suggests that the ~80 Hz oscillation originates from entorhinal cortex inputs to deeper CA1 layers, while the ~140 Hz oscillation reflects CA1 activity in superficial layers. We further show that the ~140 Hz oscillation differs from sharp-wave associated ripple oscillations in several key characteristics. Our results demonstrate the existence of novel theta-associated high-frequency oscillations, and suggest a redefinition of fast gamma oscillations